SYNTHESIS AND INVESTIGATION OF LANTHANIDES TETRAKIS-COMPLEXES WITH DIMETHYL-P-TOLUILSULPHONILAMIDOPHOSPHATE: UDC 546.65+539.26+535.37 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
The raw of lanthanide (III) coordination compounds with dimethyl-p-toluilsulphonilamidophosphate of the composition Na[LnL4],where Ln = La-Lu (except Pm); HL = p-CH3(C6H4)SO2N(H)P(O)(OCH3)2 – dimethyl-p-toluylsulphonylamidophosphate have been synthesized and isolated in crystalline state. Based on the IR spectra the bidentate coordination of ligand L- via the oxygens of phosphoryl andsulphonyl has been concluded. The complex Na[LaL4] was investigated by means X-ray diffraction. The coordination sphere of lanthanum atom has been characterized as distorted dodecahedron.
Keywords: -